Indonesian Language Teachers' Efforts in Building a Culture of Literacy and Reading Interest at SDN Bojong Menteng 2 - Hatima, Yoma; Ummah, Inayatul (International Journal of Management and Education in Human Development, 2025)
This study aims to describe the efforts of Indonesian language teachers in forming a culture of literacy and increasing students' interest in reading at SDN Bojong Menteng 2. The low interest in reading among elementary school students remains a major challenge in the world of education, so a strategic role of teachers is needed in providing meaningful learning. This study uses a qualitative approach with a case study method. The research subjects were Indonesian language teachers and students in grades IV and V, with data collection techniques through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that Indonesian language teachers made several efforts in forming a culture of literacy , including: (1) making reading activities a habit for 15 minutes before learning begins; (2) utilizing the classroom reading corner as a means of independent reading; (3) giving simple book review assignments; (4) integrating reading texts into Indonesian language learning; and (5) holding literacy activities such as poetry reading and storytelling competitions. Supporting factors for the success of these activities were the support of the principal and the availability of sufficient reading books. However, obstacles faced included the lack of variety of reading materials appropriate to the students' ages and low reading motivation from the family environment. This study concludes that the role of teachers is crucial in shaping a culture of literacy and students' interest in reading, although synergy is needed between schools, parents, and the community so that a culture of literacy can be sustainable.